Ответ:
Раскрываем скобки и собираем подобные члены .
[tex]1.1)\ \ -2(3x-2y)-5(2y-3x)=2(2y-3x)-5(2y-3x)=(2y-3x)\cdot (2-5)=\\\\=-3\cdot (2y-3x)=9x-6y\\\\2)\ \ (x^2-1)\cdot 3x-(x^2-2)\cdot 2x=3x^3-3x-2x^3+4x=x^3+x\\\\3)\ \ 2(3a^2-4a+8)=6a^2-8a+16\\\\4)\ \ (3a-5b+bc)\cdot (-3)=-9a+15b-3bc\\\\5)\ \ (9-a)(8+a-b)=72+9a-9b-8a-a^2+ab=-a^2+ab+a-9b+72[/tex]
Пользуемся формулами [tex]a^2-b^2=(a-b)(a+b)[/tex] и
[tex](a+b)^2=a^2+2ab+b^2[/tex] .
[tex]2.1)\ \ 3x^2-12=3(x^2-4)=3(x-2)(x+2)\\\\2)\ \ 2a^2+4ab+2b^2=2\cdot (a^2+2ab+b^2)=2\cdot (a+b)^2\\\\3)\ \ -a^2-2a-1=-(a^2+2a+1)=-(a+1)^2\\\\4)\ \ 18a^2-27ab+14ac-21bc=9a(2a-3b)+7c(2a-3b)=(2a-3b)(9a+7c)\\\\5)\ \ 10x^2+10xy+5x+5y=10x(x+y)+5(x+y)=(x+y)(10x+5)=\\\\=5(2x+1)(x+y)[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Раскрываем скобки и собираем подобные члены .
[tex]1.1)\ \ -2(3x-2y)-5(2y-3x)=2(2y-3x)-5(2y-3x)=(2y-3x)\cdot (2-5)=\\\\=-3\cdot (2y-3x)=9x-6y\\\\2)\ \ (x^2-1)\cdot 3x-(x^2-2)\cdot 2x=3x^3-3x-2x^3+4x=x^3+x\\\\3)\ \ 2(3a^2-4a+8)=6a^2-8a+16\\\\4)\ \ (3a-5b+bc)\cdot (-3)=-9a+15b-3bc\\\\5)\ \ (9-a)(8+a-b)=72+9a-9b-8a-a^2+ab=-a^2+ab+a-9b+72[/tex]
Пользуемся формулами [tex]a^2-b^2=(a-b)(a+b)[/tex] и
[tex](a+b)^2=a^2+2ab+b^2[/tex] .
[tex]2.1)\ \ 3x^2-12=3(x^2-4)=3(x-2)(x+2)\\\\2)\ \ 2a^2+4ab+2b^2=2\cdot (a^2+2ab+b^2)=2\cdot (a+b)^2\\\\3)\ \ -a^2-2a-1=-(a^2+2a+1)=-(a+1)^2\\\\4)\ \ 18a^2-27ab+14ac-21bc=9a(2a-3b)+7c(2a-3b)=(2a-3b)(9a+7c)\\\\5)\ \ 10x^2+10xy+5x+5y=10x(x+y)+5(x+y)=(x+y)(10x+5)=\\\\=5(2x+1)(x+y)[/tex]